(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
This article examines the science of numerology, how it was founded and divided into several branches. And how it is necessary to develop this science, which is relevant today